Internet of Things in Automotive Safety - Kodym Oldřich; Kavka Libor; Hrouda Matěj; Neradilová Hana (Logi, 2025)
The principles and practices of Industry 4.0 are increasingly promoted across all areas of management and control. Effective control relies on having the right information and knowledge in the right place, at the right time, and in the appropriate structure. The implementation of Industry 4.0 procedures contributes to addressing information gaps, creating conditions for ensuring optimal decision-making support at all levels, from real-time control of production processes, through the level of tactical management to long-term strategic development management. The Internet of Things (IoT) represents a significant (r)evolution in data acquisition and data quality. Collected data is transmitted to information systems at relevant levels, verified, pre-processed, and presented in a suitable format for various management/control levels. The article reflects typical examples of how IoT enhances the quality of individual sub-processes (logistics), which can have a significant impact on the safety of transport processes. The primary focus is on road transport, but the study also considers its role in the field of interaction of transport within production processes. The authors conclude that automation of data collection from processes, leveraging information and communication technologies have a significant impact specifically on transport process.